"If I'm at home, I do it at home": Qualitative study on HIV self-testing among transgender women in Argentina. (January 2023) - De Luca, Amalia; Zalazar, Virginia; Salusso, Diego; Frontini, Emilia; Fabian, Solange; Cardozo, Nadir Fernana; Cesar, Carina; Cahn, Pedro; Sued, Omar; Aristegui, Inés
Background: Evidence among key populations supports acceptability of HIV self-testing (HIVST) due to its privacy and convenience. However, insufficient research has been done among transgender women (TGW), especially in Latin America. Consequently, the aim of this study was to explore the acceptability, perceptions and recommendations for HIVST implementation among TGW in Buenos Aires. Methods: A focus group was conducted in July 2019. Particpants were invited to touch and learn about a displayed HIVST kit. The following main topics were explored: acceptability, reasons for seeking self-testing, preferences for training, distribution, periodicity and recommendations for HIVST implementation. Results: The sample consisted of 12 TGWs; mean age of 26 years (IQR = 22–28); 66% had history of sex-work. The main motivations for seeking HIVST were convenience, privacy, and usage to reduce stigma and discrimination by health-care providers. Recommendations for HIVST were: distribution from primary health centers and trans-sensitive centers; affordable price; assistance by peer health promoters; and the provision of clear written and video instructions. Conclusions: Tailored implementation of HIVST can increase HIV testing rates, early detection, and linkage to HIV-care in this high-prevalence group. This study provided community-driven suggestions to inform and adapt an HIVST feasibility pilot study and future implementation in Argentina.